Using large-scale genomics to improve grain yield in bread wheat forming part of a MS-MARS pre-breeding scheme - Mulweli Judy, Mudau (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScAgric)--Stellenbosch University, 2021.